2012
DOI: 10.1097/paf.0b013e31821a88c4
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Blunt Force Injury Homicides of Children Aged 0 to 5 Years in Bexar County, Texas, From 1988 to 2009

Abstract: It is essential that clinical physicians, medical personnel, medical examiners, and law enforcement agencies understand the types of injuries seen and demographics of children affected by intentional blunt force as this understanding can be crucial to the death and/or criminal investigations. An understanding of the injuries can also assist in drawing conclusions regarding how those injuries could have been sustained. This study discusses the types and patterns of injuries seen in blunt force homicides in chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…If a vein were to rupture, large volumes of subdural bleeding would be expected. However, autopsy findings in children report collections ranging from 1 to 80 mL, with 75% less than 25 mL and 50% less than 10 mL [33]. These small, thin films of subdural blood seem clinically insignificant and inconsistent with bridging vein rupture.…”
Section: Discussionmentioning
confidence: 99%
“…If a vein were to rupture, large volumes of subdural bleeding would be expected. However, autopsy findings in children report collections ranging from 1 to 80 mL, with 75% less than 25 mL and 50% less than 10 mL [33]. These small, thin films of subdural blood seem clinically insignificant and inconsistent with bridging vein rupture.…”
Section: Discussionmentioning
confidence: 99%
“…AHT is largely restricted to infants and males. Children aged <1 year are more likely to suffer brain injuries usually caused by CM than accidents [ 19 ]. Results from our study are consistent with those of Parks et al who reported most children who have fatal AHT aged <12 months and are males [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…From the AIS-data, we retrieved the number of lacerations in each victim and the Injury Severity Score (ISS). The normal grouping of ISS is "minor (1-3)," "moderate (4-8)," "serious (9)(10)(11)(12)(13)(14)(15)," "severe (16-24)," and "critical (25-75)" [18]. To better suit the homicide victim population that has few victims with low scores, we define three ISS categories: "low (1-24)," "medium (25-44)," and "high (45-75)".…”
Section: Materials S and Me Thodsmentioning
confidence: 99%
“…Blunt force trauma is often used in interpersonal violence and is a common homicide method [1][2][3][4][5][6][7][8][9][10][11][12][13]. In blunt force homicide, the blunt force trauma is inflicted in three different ways:…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation